The Impact of The Indonesia Pintar Program (PIP) on The Decision to Continue Education to Higher Education in Denpasar City - bunga, made destia bunga maharani; Putu Ayu Pramitha Purwanti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The Indonesia Pintar Program is a government initiative aimed at addressing the educational needs of disadvantaged students, ensuring they receive adequate schooling. This study investigates how the program influences students' decisions to pursue higher education in Denpasar City. Conducted using the Slovin technique, the research sampled 100 PIP recipients from 12th grade during the 2022–2023 academic year in Denpasar City. Data was collected via a questionnaire using a survey approach, and analyzed using binary logistic regression. The findings indicate that parental wealth positively and significantly influences the decision to pursue higher education, while the social environment also plays a positive role. Conversely, the number of dependents negatively impacts this decision. Additionally, parental education positively affects the likelihood of seeking higher education. Overall, the Indonesia Pintar Program provides underprivileged children with essential educational resources, encouraging them to value education beyond secondary school.